An integrated service for teenagers - Vanzetto, M.; Rodinò, R.; Santoro, M. M.; Frascarelli, T. (Medicina e Morale, 1994)
From 1993, the cooperative "Animazione Verderocca" (ANVER), Rome (ltaly) started up a free, integrated Service for adolescents, in a generai surgery. The aim of the initiative was to set up an easy admittance and open to all Service, that become not only a rcference point to resolve doubts and questions by adolescents, but also: 1) a proposal to changing a t risk-behaviors and 2) an attempt to making primary prevention of youthful deviancies. A multidisciplinary work group is a fundamental characteristic of the Service and means to focus the attention on the whole person and not only on the symptom, from the point of view of a global concept of health. The data shows that 71 adolescents, 64 girls (90%) and 7 boys (l 0% ), were examined. 368 services were carried out, at qualitative level rather than quantitative. The adolescent's demand was met by work group and redefined with the psychological advice also on the same formulation of the demand. This work, proposed by the work group of the Service, is lived by users as a right integration or reading of own's demand, since the constancy of the follow-up by adolescents and the advertising the Scrvice by teenagers with their friends.